2022
DOI: 10.3389/fpsyg.2021.769175
|View full text |Cite
|
Sign up to set email alerts
|

Tourists’ Health Risk Threats Amid COVID-19 Era: Role of Technology Innovation, Transformation, and Recovery Implications for Sustainable Tourism

Abstract: Technology innovation has changed the patterns with its advanced features for travel and tourism industry during the outbreak of COVID-19 pandemic, which massively hit tourism and travel worldwide. The profound adverse effects of the coronavirus disease resulted in a steep decline in the demand for travel and tourism activities worldwide. This study focused on the literature based on travel and tourism in the wake global crisis due to infectious virus. The study aims to review the emerging literature criticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(67 citation statements)
references
References 171 publications
(178 reference statements)
0
65
0
2
Order By: Relevance
“…The research is in line with the previous survey-based studies ( Abbas et al, 2019 ; Mamirkulova et al, 2020 ; Mubeen et al, 2020 , 2021 ; Aman et al, 2022 ; Azizi et al, 2021 ). Investigators interviewed 150 female entrepreneurs, including 75 urban and 75 rural participants and followed survey procedure to receive data ( Liu et al, 2021 ; Mubeen et al, 2021 ; Wang et al, 2021 ; Li et al, 2022 ). The study recruited respondents through the snowball sampling technique from a population of purposively selected female-run businesses.…”
Section: Methodsmentioning
confidence: 99%
“…The research is in line with the previous survey-based studies ( Abbas et al, 2019 ; Mamirkulova et al, 2020 ; Mubeen et al, 2020 , 2021 ; Aman et al, 2022 ; Azizi et al, 2021 ). Investigators interviewed 150 female entrepreneurs, including 75 urban and 75 rural participants and followed survey procedure to receive data ( Liu et al, 2021 ; Mubeen et al, 2021 ; Wang et al, 2021 ; Li et al, 2022 ). The study recruited respondents through the snowball sampling technique from a population of purposively selected female-run businesses.…”
Section: Methodsmentioning
confidence: 99%
“…The development of new sick road according to Mamirkulova et al ( 2020 ) is observed improve residence quality of life, hence achieving the development of sustainable tourism since the infrastructure is enhanced. On the other hand, the Covid-19 outbreak together with lockdown measures that has been put in place to curb the spread of the disease have had negative impact on the tourism sector since traveling has been restricted (Mamirkulova and Mi 2022 ; Wang et al 2021a ; Zhou et al 2022 ; Li et al 2022 ; Liu et al 2021a ; Fu 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The COVID-19 pandemic has a direct impact on nearly every sector of the economy ( Maqsood et al, 2021 ). The devastating impact of the coronavirus pandemic on travel and tourism around the world has resulted in a severe drop in tourist demand ( Li, Wang, Duan, & Mubeen, 2021 ). As the repercussions of the tourism hit, the hotel industries are among the worst-hit worldwide.…”
Section: Literature Reviewmentioning
confidence: 99%